Comparative HPLC Enantioseparation of Thirty‐Six Aromatic Compounds on Four Columns of the Lux® Series: Impact of Substituents, Shapes and Electronic Properties. Issue 11 (26th July 2013) - Peluso, Paola; Cossu, Sergio
ABSTRACT With the aim to define a combined computational/chromatographic empirical approach useful for the high‐performance liquid chromatography (HPLC) method development of new chiral compounds, 36 racemic aromatic compounds with different chemical structures were used as test probes on four polysaccharide‐based chiral stationary phases (CSPs) of the Lux series, namely Lux Cellulose‐1, Lux Cellulose‐2, Lux Cellulose‐4, and Lux Amylose‐2, using classical n‐hexane/2‐propanol mixtures as mobile phase. Electrostatic potential surfaces (EPSs) determined using Density Functional Theory (DFT) calculations were used to derive size, shape, and electronic properties of each analyte. Then a comparative HPLC screening was carried out in order to evaluate the impact of substituents, shapes, and electronic properties of the analytes on the chromatographic behavior as the column changes. The four CSPs showed good complementary recognition ability. The elution sequence was determined in 30 cases out of 36. The success rate to afford baseline separations (Rs ≥ 1.5) was estimated: 29 compounds out of 36 showed baseline enantioseparation on at least one of the four selected CSPs. The combined computational‐chromatographic screening furnished useful collective structure‐chromatographic behavior relationships and a map of the chiral discrimination abilities of the considered CSPs towards the analytes. On this basis, the chromatographic behavior of new analytes on a set of polysaccharide‐based CSPs can be mapped through the qualitative correlation of chromatographic parameters (k, α, Rs) to computed molecular properties of the analytes. Chirality 25:709–718, 2013. © 2013 Wiley Periodicals, Inc.